2019
DOI: 10.1016/j.nedt.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Analysing training in gender-based violence for undergraduate nursing students in Spain: A mixed-methods study

Abstract: Background: Health-care professionals, and nurses especially among them, play an essential role in the health sector's response to gender-based violence. To be able to successfully address this major public health issue they need specific training in the topic. Objective: To analyse training on gender-based violence that nursing students receive at universities in Spain. Design: Mixed-methods approach Setting: Spain Methods: Systematic review of public documents followed by in-depth interviews with university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 18 publications
3
18
0
6
Order By: Relevance
“…This highlights positive results and supports the ideas presented by various authors about the need for education in initial training [39]. However, it is necessary to take into account the existence of great dissimilarities among the different education/training programs in different Spanish universities [36], and it is important to conduct a deep analysis into the diverse programs and their benefits. Some research points to the intervention and training of students as a tool for the prevention of risk situations [41].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This highlights positive results and supports the ideas presented by various authors about the need for education in initial training [39]. However, it is necessary to take into account the existence of great dissimilarities among the different education/training programs in different Spanish universities [36], and it is important to conduct a deep analysis into the diverse programs and their benefits. Some research points to the intervention and training of students as a tool for the prevention of risk situations [41].…”
Section: Discussionsupporting
confidence: 81%
“…They mostly analyze different ways in which gender-based violence may be expressed in universities [1] and examine abusive and discriminatory behaviors towards women in the university environment. In this university context and after the review of several pieces of research, we found a common problem independent of the field of study from research focused on degrees related to the Social Sciences, such as those related to Health Sciences [36]. Specific focus should be given to studies into teacher training [37][38][39][40], highlighting the need to incorporate education into gender and sexual diversity in initial teacher training, as they will have a primary responsibility for developing a comprehensive education in their future students [38].…”
Section: Introductionmentioning
confidence: 90%
“…However, the detection rate of GBV is still low in these services [65]. Therefore, more formal training on this type of violence is needed for both nursing students and registered nurses to improve care for these women [10,14,26,29,60,66]. Therefore, we recommend including a high-fidelity clinical simulation methodology for training undergraduate nursing students and registered nurses in GBV victim management.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, most nursing education plans include specialized training in GBV in their curricula, although the topics covered tend to be heterogeneous [29]. Nevertheless, nursing education is the first step for providing a response to GBV.…”
Section: Introductionmentioning
confidence: 99%
“…Literatürde, standartlaştırılmış hasta senaryoları, akran eğitim programları, mağdurlarla yapılan görüşmeler ve sosyal hizmetlere yerleştirmeler gibi pratik eğitimler ile mevcut durumun daha iyi yönetilebileceği öne sürülmüştür. [17] Bizim çalışmamıza katılan hekimlerin çalıştığı kurumda, kadına yönelik şiddet için kullanılan talimat /prosedürü bulunanların oranını çok düşük olduğu saptandı. HEKYSBTÖ puanı ile, çalışılan kurumda kadına yönelik şiddet için kullanılan talimat/ rosedürü olması arasında istatistiksel olarak anlamlı ilişki saptanmadık.…”
Section: Bulgularunclassified